2000
DOI: 10.1021/la0003544
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Electrostatic Potential Induced by Anion-Dominated Partition into Zwitterionic Micelles and Origin of Selectivity in Anion Uptake

Abstract: The surface potentials of n-dodecyltrimethylammoniopropanesulfonic acid (DDAPS) micelles in various electrolytes have been evaluated by capillary electrophoresis. This zwitterionic micelle has an inner cationic surface and an outer anionic surface and accommodates anions better than cations, indicating that a negative surface potential is induced by anion-dominated partition. Selectivity terms, i.e., solvation changes of ions and ion association between ions and charged groups in the DDAPS micelles, are introd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
67
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(73 citation statements)
references
References 37 publications
6
67
0
Order By: Relevance
“…[46][47][48][49] The zeta potential of a micelle is one of the most useful physicochemical properties of a micelle. Although there is a debate on whether the shear plane corresponds to the real surface or not, the rigorous definition of the micellar surface is of no physical significance because micelles are dynamic systems that are subject to continuous thermal perturbation.…”
Section: -45mentioning
confidence: 99%
See 1 more Smart Citation
“…[46][47][48][49] The zeta potential of a micelle is one of the most useful physicochemical properties of a micelle. Although there is a debate on whether the shear plane corresponds to the real surface or not, the rigorous definition of the micellar surface is of no physical significance because micelles are dynamic systems that are subject to continuous thermal perturbation.…”
Section: -45mentioning
confidence: 99%
“…However, in an electrolyte, a relatively large charge is induced by the imbalance between the partition of cations and that of anions into the micelle. 46,51 Figure 7 summarizes the zeta potential of DDAPS micelles measured in various electrolytes. Interestingly, negative potential is induced in any electrolyte, and the nature of a cation affects the zeta potential only slightly.…”
Section: -45mentioning
confidence: 99%
“…Moore et al also indicated by fluorophotometry that the binding constants of an anionic dye to nonionic surfactant micelles 9 were larger than that of cationic crystal violet. 8 Okada et al have indicated the selective partition of anions to nonionic polyoxylated surfactant micelle 29 and to zwitterionic surfactant micelle 30,31 through the negative ζ potential of the micelle. In this study, the weak binding affinity of nonionic Brij 58 micelle toward cationic N-alkylpyridinium ions has also been investigated with the analysis through the electrophoretic mobility.…”
mentioning
confidence: 99%
“…The nature of these anions should play a crucial role in the selectivity for the amphoteric ion-exchange resin, similar to that for amphoteric micelles. 17,18 The affinity of an anion to the amphoteric ionexchange resin should be correlated with both the dehydration energy of the anion and the electrostatic interaction between the anion and the functional group. 19,20 …”
Section: Analytical Sciences September 2008 Vol 24mentioning
confidence: 99%